Angielskie strofy i polska lutnia. O przekładach „Melodii hebrajskich” George’a Gordona Byrona pióra Antoniego Edwarda Odyńca - Nowak, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article discusses the translation of four poems by George Gordon Byron: Vision of Belshezzar, The Wild Gazelle, Oh! Weep for Those, On Jordan’s Banks from the collection Hebrew Melodies published in 1816 as a result of the poet’s cooperation with the composer Isaac Nathan. The Polish translations by Antoni Edward Odyniec were published in his collections in 1826 (Vision of Belshezzar) and 1832 (the remaining ones). The first part of the text is dedicated to the circumstances in which the originals were written. The second part constitutes a detailed analysis of the translation choices of Odyniec, which places them in the context of Polish poetry of the post-partitions period (among others, poems by Jan Paweł Woronicz and Adam Jerzy Czartoryski) and in the context of translation studies (Lawrence Venuti, Stanisław Barańczak, André Lefevere).